UTILITY OF ASSESSMENT SERUM LEVELS OF VEGF, bFGF AND PDGF-BB AS SUGGESTED ANGIOGENESIS BIOMARKERS PANEL TOOL IN PATIENTS WITH BREAST CANCER - 4Osama Elbaz, 1Nahla Anber, 2Ahmed EL-Sebaie, 3Shaker Mousa (Journal of Biomedical and Pharmaceutical Research, 2016)
Introduction: Breast cancer is the commonest cause of cancer death in women worldwide. A shift in the angiogenic balance allows the up-regulation of several pro-angiogenic factors, which by ways of mutual interactions stimulate tumor angiogenesis.  Angiogenic factors are produced directly by tumor through the cancer cells or indirect by inflammatory cells that infiltrate tumor. Tumoural angiogenesis is essential for the growth and metastases of breast cancer cells.Aim: The aim of the present study was to asses vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF) and platelet-derived growth factor (PDGF-BB) serum levels in breast cancer patients as promising suggested panel of tool of some angiogenesis markers assisted by Bio- Plex Pro assays for diagnosis and prognosis performance in breast cancer, also as predictors to identify subgroups of patients fitting into different treatment to improve clinical outcomeMethod: Serum samples were collected from 68 breast cancer female patients; 32 pre-treatment and 36 under conventional chemo-radiotherapy and 10 healthy female donors as controls. Under treatment patients classified according to therapy related number of cycles regimen received to 1-4 (n=10), 5-8 (n=18), and > 8 cycles (n=8). The levels of the angiogenic markers, VEGF, bFGF and PDGF-BB, were assessed by Bio-Plex Pro assays that quantify multiple protein biomarkers.Results: There was a significant increase in VEGF and PDGF-BB (P1< 0.05) and non significant elevated bFGF (p1>0.05) in breast cancer pretreatment patients compared to controls. In patients under treatment there was a non significant elevated level in median values for each marker than the base line measurement (P2 > 0.05). A highly significant reduction serum levels for each of bFGF and PDGF-BB (P3< 0.001) and significant reduction (P3< 0.05) for VEGF after conventional adjuvant therapy treatment compared with pretreated patient serum levels. Those patients received 1-4 cycles regimen elevated non-significant median values (P4 > 0.05) for each of FGF and PDGF-BB, while VEGF showed significant elevated serum level (P4 < 0.05) in compare to baseline measurement. Those patients received 5-8 cycles regimen treatment identified non significant reduction (P5 > 0.05) in median values with baseline level of control subjects. Those patient received more than 8 cycle regimen reviled significant reduction for bFGF (P6 < 0.05) and significant elevated value (P6 > 0.05) for VEGF and non-significant (P6 > 0.05) reduction serum level for PDGF-BB compared with base line measuring value.Conclusions: our results confirmed that suggested panel tool of VEGF, bFGF and PDGF-BB serum levels assessed by Bio-Plex ® Pro Assays for Angiogenesis Factors Quantification is useful for the early detection of breast cancer within screening programs, suitable for prospective studies for breast cancer diagnosis and/ or recurrence of tumor, in prognosis and monitoring members of high- risk breast cancer families. Also, our suggested panel angiogenesis marker tool is useful for identifying subgroups of patients fitting into different treatment to improve clinical outcome. Key words: Breast cancer; Bioplex; VEGF; bFGF; PDGF-BB